Systematic Literature Review: Pesenggiri Piil Philosophy in School Principal Leadership - Magdalena, Frida; Hariri, Hasan; Sari, Siti Rahma (Journal of Educational Management Research, 2025)
This research examines the role of Piil Pesenggiri's philosophy in shaping school principal leadership, with an emphasis on local wisdom values within the Lampung cultural context. Values such as nemui nyimah, sakai sambayan, nengah nyappur, and nickname adok are believed to strengthen the principal's moral and social dimensions. The research employs a Systematic Literature Review (SLR) using the PRISMA approach, analyzing 20 peer-reviewed articles published within the last five years on cultural value-based leadership. Findings reveal that Piil Pesenggiri contributes to inclusive, moral, and collaborative leadership. Principals who embody these values are perceived as more open, adaptable, and respected by the school community. However, challenges include the absence of local culture-based training and pressures from national education policies. The study concludes that integrating Piil Pesenggiri into leadership can enhance ethical and transformative leadership qualities, fostering a more inclusive and contextually relevant learning environment. Policy support and training programs are needed to embed local wisdom into Indonesia’s educational leadership system.